Pengelolaan Zakat Produktif Sebagai Pembangunan Kesejahteraan Masyarakat Secara Berkelanjutan Di Indonesia - Zakariya, A. Fahmi; Syuhana, Eka; Rosida, Ika Nazilatur (Al-Musthofa: Journal of Sharia Economics, 2024)
This article with title “Pengelolaan Zakat Produktif sebagai Pe mbangunan Kesejahteraan Masyarakat Cecara Berkelanjutan di Indonesia”. Management of productive zakat is one of the efforts to distribute zakat which is effective in helping to solve social problems, and encourage the development of community welfare. In order for this goal to work, productive zakat must be managed appropriately, so that the problem of poverty in the community can be reduced. The method used in this paper uses a qualitative method with a literature approach that uses supporting data that is analyzed descriptively. The results of this writing explain the management of productive zakat, and zakat in the development of community welfare in a sustainable manner. From the results of this paper, it can be seen how the efforts of community empowerment are supported by the management of productive zakat. In this case, it focuses on the distribution of productive zakat for zakat recipients (mustahiq) so that their economy can be built independently and their achievements can become zakat payers (muzakki).